PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAPKINERJA PEGAWAI PEMERINTAH DI DINAS KESEHATAN PROVINSI JAMBI - Johannes .; Dewi Sri Ningsih Ujung (Jurnal Dinamika Manajemen, 2013)
This research examines the effect of job satisfaction and organizational commitment on employee performace.Sample has chosen at the Provincial Healt Service that consists of 72 persons.Statistical analyisis used MultipleRegressions thatconsists of simultaneus test and parital test.Based on the analysis it is found that job satisfaction and organizational commitment simultaneously have a significant effect on employee performance.Hence, employee preformance could be improved by improve job satisfaction and organizational comitment. Organizational comittment actually has distinguised condition allowed ther official organization structur. So, formal leader has to encourage employee to be more performed throug job satisfaction conditions. Keywords: employee performance, job satisfaciton and organization commitment